Upaya Meningkatkan Hasil Belajar Siswa melalui Penerapan Pembelajaran Student Facilitator and Explaining di SMA Negeri 1 Gondang Bojonegoro - Ninik Hartati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to improve the learning outcomes of Biology subjects using the Student Facilitator and Explaining learning model. This research uses action research method with two cycles covering the process of planning, implementation, sharpening, and reflection. The subject of the study was a grade X student of MIPA I SMA Negeri 1 Gondang Bojonegoro. The results showed a significant increase in student learning outcomes in cycle I by 52.88% increased to 86.21% in cycle II. The implementation of student facilitator and explaining learning model can also improve the quality of Biology learning by 33.33%. Student Facilitator and Explaining learning model can be applied to the learning process.